The Role of Fluid Shear and Metastatic Potential in Breast Cancer Cell Migration - Riehl, Brandon D. (J Biomech Eng, 2020)
During the migration of cancer cells for metastasis, cancer cells can be exposed to fluid shear conditions. We examined two breast cancer cell lines, MDA-MB-468 (less metastatic) and MDA-MB-231 (more metastatic), and a benign MCF-10A epithelial cell line for their responsiveness in migration to fluid shear. We tested fluid shear at 15 dyne/cm(2) that can be encountered during breast cancer cells traveling through blood vessels or metastasizing to mechanically active tissues such as bone. MCF-10A exhibited the least migration with a trend of migrating in the flow direction. Intriguingly, fluid shear played a potent role as a trigger for MDA-MB-231 cell migration, inducing directional migration along the flow with significantly increased displacement length and migration speed and decreased arrest coefficient relative to unflowed MDA-MB-231. In contrast, MDA-MB-468 cells were markedly less migratory than MDA-MB-231 cells, and responded very poorly to fluid shear. As a result, MDA-MB-468 cells did not exhibit noticeable difference in migration between static and flow conditions, as was distinct in root-mean-square (RMS) displacement—an ensemble average of all participating cells. These may suggest that the difference between more metastatic MDA-MB-231 and less metastatic MDA-MB-468 breast cancer cells could be at least partly involved with their differential responsiveness to fluid shear stimulatory cues. Our study provides new data in regard to potential crosstalk between fluid shear and metastatic potential in mediating breast cancer cell migration.